Research on the cultural confidence of college students in the new era - Ma, Qinjuan; Wang, Pingshui (IJRDO- Journal of Educational Research, 2018)
A nation will be strong if its culture is strong. To achieve the great rejuvenation of the Chinese nation, we must have strong support for cultural prosperity and prosperity. In the new era, college students’ "cultural confidence" has become a problem that cannot be ignored. "Cultural confidence" is the affirmation and confidence of Chinese traditional culture, which is beneficial to the self-growth of college students and the construction of the mainstream ideology, thus realizing the "dream of a powerful country". Therefore, it is an important way to strengthen the "theoretical confidence" of the college students by strengthening the guidance of the mainstream ideology of the society, giving full play to the active role of the network participation and promoting the traditional culture of the Chinese nation. Key words: New era; college students; cultural confidence